Diagnostic Pathway to Nonsense Mutation Dystrophinopathy: A Tertiary-Center, Retrospective Experience - Ardıçlı, Didem; Haliloğlu, Goknur; Alikaşifoğlu, Mehmet; Topaloğlu, Haluk (Neuropediatrics, 2019)
Up to 15% of Duchenne's muscular dystrophy (DMD) is caused by nonsense mutations (nm-DMD). In this study, we aimed to evaluate the age at diagnosis, presentations, and diagnostic approach in 43 nm-DMD boys. The mean age at presentation and diagnosis was 3 years and 4 years, respectively. Presenting signs or symptoms were asymptomatic creatine kinase (CK) elevation (40%), muscle weakness (30%), motor delay (18%), and walking difficulties (12%). Multiplex polymerase chain reaction (PCR) of the most commonly deleted exons were negative (n = 17), and muscle biopsy was consistent with dystrophinopathy (n = 24). In all patients, multiplex ligation-dependent probe amplification (MLPA) followed by direct sequencing of all exons, revealed nm-DMD. Mean age at genetic diagnosis was 6 years 8 months. Patients were evaluated in two-time periods, between 2006 and 2011 (Group I: n = 10) and 2011 and 2017 (Group II: n = 33). The mean age at diagnosis/genetic confirmation in Group I and in Group II was 3 years 9 months/10 years, and 4 years 1 month/5 years 9 months, respectively. Most frequently performed first step diagnostic tests in Group I and Group II were muscle biopsy and MLPA.Our study reflects the change in the age at genetic diagnosis and diagnostic approach to nm-DMD depending on the advances and availability of genetic testing.
Keywords: Duchenne's muscular dystrophy; molecular diagnosis; nonsense mutation; diagnostic approach